A Study on cross-border M&A and FDI policy in Korea - Kwon, Ki Yul (KDI School, 2000)
This paper examines the main drivers of cross-border M&A activities in Korea and suggests policy implications to promote them in the future. Due to the favorable policy environment of FDI and the removal of foreign ownership restrictions after the IMF crisis, cross-border M&A in Korea is expected to increase significantly. Cross-border M&A can contribute to the national economy by attracting foreign capital and management know-how, and enhance firm value by putting pressure on firms to be more responsive to shareholder value. This study also examines the strategic motivations for cross-border M&A and some of the key success factors by analyzing the case of Daesang’s Lysine Business and Samsung Heavy Industries’ Construction Equipment Business. Some policy implications derived from the case studies will be suggested in the conclusion.
Thesis(Master) --KDI School:Master of Business Administration,2000